Kualitas laporan keuangan dan faktor-faktor yang mempengaruhinya - Sulistyawati, Ardiani Ika; Santoso, Aprih; Sholohah, Silvia Almar’atus (Indonesia Accounting Journal, 2019)
The purpose of this study is to analyze the influence of implementation Good Government Governance, Government Accounting Standards, Monitoring, Quality of Local Government Reform, Human Resource Competency, and Financial Accounting System on the Quality of Financial Statements in DPKAD Semarang City. The object in this study is SKPD staff in DPKAD Semarang City. This study uses primary data obtained by spreading the questionnaire. Sampling was done by using purposive sampling method and the sample size was 49 respondents. The data analysis was done by using multiple regression with the help of SPSS V20 software. The independent variables in this study consisted of Good Government Governance, Government Accounting Standards, Monitoring, Quality of Local Government Reform, Human Resource Competency, dan Financial Accounting System which the dependent variable is The Quality of The Financial Statements. The results of this study show that implementation of Monitoring to influence the quality of Financial Statements. But implementation of Good Good Government Governance, Government Accounting Standards, Quality of Local Government Reform, Human Resource Competency, dan Financial Accounting System have not influence the Quality of Financial Statements.